Filosofi Pembelajaran Menulis Laporan Pengamatan dengan Metode Proyek pada Siswa SD Kelas 6 - Agus Abdurohim; Ade Sugiawan (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
Learning to write observation reports in grade 6 SDN Harjasari 2 shows a problem. These problems were found in the assessment of student activities and learning outcomes. This is because when delivering learning materials, teachers use learning methods that do not train students' thinking skills. The corrective action taken is to apply the project method. The project method is a way of teaching by providing learning activities to students, by providing opportunities for students to choose, design and lead their thoughts and work. This research is classroom action research. The initial data explained that 15 students had completed or 54% of the total number of 28 students. The action was carried out in three cycles because the target was only achieved in the third cycle. From the research results obtained, it can be concluded that the project method is able to improve the skills of writing observation reports, and philosophically students have been able to think scientifically with the project method steps.